Diagnostic pathways in multiple myeloma and their relationship to end organ damage: an analysis from the Tackling Early Morbidity and Mortality in Myeloma (TEAMM) trial. (15th August 2020) - Atkin, Catherine; Iqbal, Gulnaz; Planche, Tim; Pratt, Guy; Yong, Kwee; Wood, Jill; Raynes, Kerry; Low, Eric; Higgins, Helen; Neal, Richard D.; Dunn, Janet; Drayson, Mark T; et al.
Summary: Multiple myeloma is associated with significant early morbidity and mortality, with considerable end organ damage often present at diagnosis. The Tackling EArly Morbidity and Mortality in Multiple Myeloma (TEAMM) trial was used to evaluate routes to diagnosis in patients with myeloma and the relationship between diagnostic pathways, time to diagnosis and disease severity. A total of 915 participants were included in the study. Fifty‐one per cent were diagnosed by direct referral from primary care to haematology; 29% were diagnosed via acute services and 20% were referred via other secondary care specialties. Patients diagnosed via other secondary care specialties had a longer diagnostic interval (median 120 days vs. 59 days) without an increase in features of severe disease, suggesting they had a relatively indolent disease. Marked intrahospital delay suggests possible scope for improvement. A quarter of those diagnosed through acute services reported >30 days from initial hospital consultation to haematology assessment. Participants diagnosed through acute services had poorer performance status ( P  < 0·0001) and higher burden of end organ damage ( P  < 0·0001) with no difference in the overall length of diagnostic pathway compared to those diagnosed by direct referral (median 59 days). This suggests that advanced disease in patients presenting through acute services predominantly reflects disease aggression.